Placental Implantation Sites, Uterine Anatomy, and Uterine Physiology in Relation to Postpartum Hemorrhage: A Systematic Review: Placental Site and Uterine Factors in Postpartum Hemorrhage - Ali, Dur E Shehwar; Mahmood, Anjum; Ali, Seema; Arbab, Mishkat; Cheema, Nuzhat Nazar; Jan, Rahmat Ullah (Pakistan Journal of Health Sciences, 2026)
Postpartum hemorrhage (PPH) remains a major cause of maternal morbidity and mortality worldwide. Increasing evidence suggests that the placental implantation site and uterine structural characteristics influence the effectiveness of hemostasis after placental separation, particularly in placenta previa and placenta accreta spectrum (PAS). Objectives: To systematically review human studies examining the relationship between placental implantation site, uterine anatomy, uterine physiology, and the risk of postpartum hemorrhage. Methods: This systematic review followed PRISMA 2020 guidelines. PubMed, Web of Science, and Scopus were searched for studies published between January 2018 and December 2025. Eligible studies included observational human studies and imaging-based diagnostic studies evaluating placental implantation or uterine structural or physiological factors in relation to PPH. Animal studies, case reports, and review articles were excluded. Data were extracted using a standardized form, and methodological quality was assessed using the Newcastle–Ottawa Scale. Due to heterogeneity in study design and outcome definitions, a narrative synthesis was performed. Results: Eighteen studies met the inclusion criteria. Abnormal placental implantation, particularly lower uterine segment placentation, placenta previa, pernicious placenta previa, and PAS, was consistently associated with increased PPH risk. Structural factors, including reduced myometrial thickness and disruption of the uteroplacental interface, were frequently reported contributors to excessive bleeding. Conclusions: Abnormal placental implantation and associated uterine structural changes are important contributors to postpartum hemorrhage. Antenatal imaging may assist in identifying high-risk pregnancies and guiding delivery planning.